Ten years of live surgical broadcast at Charité-MAYO conferences (2010-2019): a systematic evaluation of the surgical outcome - Altmann, Judith; Chekerov, Radoslav; Fotopoulou, Christina; Muallem, Mustafa-Zelal; Du Bois, Andreas; Cliby, William; Dowdy, Sean; Podratz, Karl; Lichtenegger, Werner; Camara, Omar; Tunn, Ralf; Cibula, David; et al. (International journal of gynecological cancer, 2022)
OBJECTIVE: The international Charité-MAYO Conference aims to promote international dialog on diagnostics, management, scientific breakthroughs, and state-of-the-art surgical procedures in gynecology and gynecologic oncology and senology. Live surgeries are a fundamental tool of interdisciplinary and international exchange of experts in their respective fields. Currently, there is a controversial and emotional debate about the true value, risks, and safety of live surgical broadcasts. The aim of the current study is to analyze peri-operative risks in patients who were operated live during the Charité-MAYO Conferences. METHODS: Live surgeries were performed by the core Charité team consisting of gynecologic oncologic surgeons, breast and plastic surgeons, partly in collaboration with visiting gynecologic oncologic surgeons. We performed a retrospective analysis of live surgeries performed during seven Charité-MAYO Conferences from 2010 to 2019 held in Berlin, Germany. Patients' files and tumor databases were analyzed as required and patients were contacted to update their long-term follow-up. RESULTS: Sixty-nine patients who were operated live were included. The types of surgery were as follows: urogynecologic procedures (n=13), breast surgery (n=21), and gynecologic oncology surgery for ovarian, uterine, vulvar or cervical cancer (n=35). Peri-operative complications were assessed according to the Clavien-Dindo classification. Despite a high rate of complete resection and the high frequency of multivisceral procedures, the rate of peri-operative complications was within the range published in the literature. Time of surgery and length of intensive unit care and hospital stay did not differ from data acquired at the home institution. CONCLUSIONS: Based on our analysis, live surgeries appear to be safe when performed within a multidisciplinary setting without an increase in surgical morbidity and mortality compared with historical controls and without compromise of patients' outcome. This is the first analysis of its kind to set the basis for patient information and consent for this type of surgeries.
Keywords: pooperační komplikace; gynekologické chirurgické výkony; lidé; nádory ženských pohlavních orgánů; výsledek terapie; retrospektivní studie; Humans; Postoperative Complications; Retrospective Studies; Genital Neoplasms, Female; Gynecologic Surgical Procedures; Treatment Outcome; ženské pohlaví; Female